Evaluating the evidence of culling a native species for conservation benefits. Issue 12 (5th October 2021) - Melton, Courtney B.; Reside, April E.; Simmonds, Jeremy S.; Mcdonald, Paul G.; Major, Richard E.; Crates, Ross; Catterall, Carla P.; Clarke, Michael F.; Grey, Merilyn J.; Davitt, Galen; Ingwersen, Dean; Robinson, Doug; et al.
Abstract: Controlling problem species for conservation can be fraught, particularly when native species are subject to lethal control. The noisy miner ( Manorina melanocephala ), has been the target of numerous lethal control efforts. Outcomes of these noisy miner removals have varied substantially, so identifying the circumstances under which they are effective is essential for ethical and effective management. We compiled data for all identified noisy miner removals ( n  = 45), including both permit‐based and unofficial removals. We investigated whether methodological and ecological factors explained the effectiveness of removals in reducing noisy miner density or increasing woodland bird richness and abundance. The only predictor of any measure of success was time between first and final culls which was positively related to reduction in noisy miner density. Surprisingly, despite removals mainly failing to reduce noisy miner density to below a threshold above which noisy miners impact smaller birds, woodland birds usually still increased. Disrupted social structure as noisy miners recolonized may have led to less effective aggressive exclusion of small birds. Further removals may not need to reduce noisy miner density to below this threshold to benefit woodland birds, but consistent monitoring and reporting would support better evaluation of effectiveness and correlates of success. Abstract : The outcomes of noisy miner removal initiatives to conserve woodland birds have varied substantially, thus identifying the circumstances under which they are effective is essential for ethical management of this native problematic species. We collected and analyzed data for all known permit‐based and unofficial noisy miner removals to identify whether methodological and ecological factors explained the effectiveness of removals in reducing population sizes and improving richness and abundance of small woodland birds. To benefit small woodland birds, noisy miner density may not need to be reduced to below the threshold at which assemblages are disrupted in unmanaged situations.